Recognition of the unripe strawberry by using color segmentation techniques - Fadhel, Mohammed Abdulraheem; Hatem, Ahmed Samit; Alkhalisy, Muhanad Abdul Elah; Awad, Fouad H.; Alzubaidi, Laith (International Journal of Engineering and Technology, 2018)
In this paper, the efficiency comparison is displayed for recognize the unripe strawberry fruit using two different methods; color thresholding and K-means clustering. Color thresholding technique includes the following steps: color thresholding, morphological enhancement and draw mark for tracking. K-means clustering comprises filtering, transform the image to L*a*b color space, binary thresholding and extract the desired strawberry region. The results explained that color thresholding gets the better of K-means in the aspect of accuracy, effectiveness, and speed of code implementation. Both interested parties are written using MATLAB (R2018a) language.